MANAJEMEN PRAKTIK KERJA INDUSTRI - Suwarni Suwarni (UNIVERSITAS BENGKULU, 2017)
This research aimed at describing the management of the industrial working practice at vocational high school 3 Lubuklinggau. The methode of study used is qualitative descriptive. The subject of the study is the principal and the staff, head of study program, work team, advisors of the the industrial working practice, instructur of industry, student, and the school’s partner. The result of the study concluded as follow: (1) the planning has been well performed, (2) the organizing was performed by the work team only, (3) students activities at the workshop by using daily journal, (4) the monitoring and evaluation were done using journal and monitoring system.